Classificação de óleos vegetais comestíveis usando imagens digitais e técnicas de reconhecimento de padrões - Milanez, Karla Danielle Tavares de Melo (2013)
This work presents a simple and non-expensive based on digital image and pattern recognition techniques for the classification of edible vegetable oils with respect to the type (soybean, canola, sunflower and corn) and the conservation state (expired and non-expired period of validity). For this, images of the sample oils were obtained from a webcam, and then, they were decomposed into histograms containing the distribution of color levels allowed for a pixel. Three representations for the color of a pixel were used: red-green-blue (RGB), hue-saturation-intensity (HSI) and grayscale. Linear discriminant analysis (LDA) was employed in order to build classification models on the basis of a reduced subset of variables. For the purpose of variable selection, two techniques were utilized, namely the successive projections algorithm (SPA) and stepwise (SW) formulation. Models based on partial least squares-discriminant analysis and (PLS-DA) applied to full histograms (without variable selection) were also employed for the purpose of comparison. For the study evolving the classification with respect to oil type, LDA/SPA, LDA /SW and PLS-DA models achieved a correct classification rate (CCR) of 95%, 90% and 95%, respectively. For the identification of expired non-expired samples, LDA / SPA models were found to the best method for classifying sunflower, soybean and canola oils, achieving a TCC of 97%, 94% and 93%, respectively, while the model LDA/SW correctly classified 100% of corn oil samples. These results suggest that the proposed method is a promising alternative for inspection of authenticity and the conservation state of edible vegetable oils. As advantages, the method does not use reagents to carry out the analysis and laborious procedures for chemical characterization of the samples are not required